Los humedales invisibles en textos de Saer y Wernicke - Leonardo Senkman (Cuadernos LIRICO)
This article explores the stories of Juan José Saer and Enrique Wernicke. Their imaginative worlds and zones of diegesis are fictions located on the Paraná riverside or the Río de la Plata shore. Nuclei of meaning (time, myth, history) make the humid areas invisible, despite the authors approaching their riversides in El río sin orillas. Ensayo imaginario and La ribera.